The vocation of healing though art - Biosca, Irene A. (Revista del Hospital Italiano de Buenos Aires, 2016)
Humanization of medical practice takes into account the patient’s experience of illness, as well as the true sense to cure, to alleviate, to heal and to care about the person. Sensitiveness comes into play in that experience. The sensitive and emotional experience is the engine of the symbolic capacity of humankind; and the symbol is the representative-affective tie and the imaginary agreement between the person and his world. Images, as symbols, cannot be reduced to the rational verbal language. Art Therapy, through those images, takes care about the person in the prevention or treatment of different diseases. Art Therapy is a health-related discipline in development around the world with an increasing number of studies supporting its positive effects. Its therapeutic tools are the stimulation of the sensitivity, the use of the image as a language, the creative play, the symbolization, and the group experience. Art Therapy incorporation in the hospital setting has a strong rationale: Art has always been along with humankind and Medicine as another vocational way to heal